Diarrhoeal diseases among adult population in an agricultural community Hanam province, Vietnam, with high wastewater and excreta re-use - Phuc Pham Duc; Hung Nguyen-Viet; Hattendorf, J.; Cam Dac Phung; Zurbrugg, C.; Zinsstag, Jakob; Odermatt, P. (Springer, 2014)
BACKGROUND: Despite the potential health risks of wastewater and excreta use as fertiliser in agriculture, it is still widespread in Vietnam. However, the importance of diarrheal risk in adults' associated with the combined exposures to both excreta and wastewater use in agriculture is largely unknown. This study was carried out to determine diarrhoeal incidence and associated risk factors among the adult population exposed to wastewater and excreta used in agriculture in Hanam province, Vietnam. METHODS: An open cohort of 867 adults, aged 16-65 years, was followed weekly for 12 months to determine the incidence of diarrhoea. A nested case-control study was used to assess the risk factors of diarrhoeal episodes. Two hundred and thirty-two pairs of cases and controls were identified and exposure information related to wastewater, human and animal excreta, personal hygiene practices, and food and water consumption was collected. RESULTS: The incidence rate of reported diarrhoea was 0.28 episodes per person-years at risk. The risk factors for diarrhoeal diseases included direct contact with the Nhue River water (odds ratio [OR] = 2.4, attributable fraction [AF] 27%), local pond water (OR = 2.3, AF 14%), composting of human excreta for a duration less than 3 months (OR = 2.4, AF 51%), handling human excreta in field work (OR = 5.4, AF 7%), handling animal excreta in field work (OR = 3.3, AF 36%), lack of protective measures while working (OR = 6.9, AF 78%), never or rarely washing hands with soap (OR = 3.3, AF 51%), use of rainwater for drinking (OR = 5.4, AF 77%) and eating raw vegetables the day before (OR = 2.4, AF 12%). CONCLUSIONS: Our study shows that professional exposure to wastewater and excreta during agricultural activities are significantly contributing to the risk of diarrhoea in adults. The highest attributable fractions were obtained for direct contact with Nhue River and local ponds, handling practices of human and animal excreta as fertilisers, lack of protective measures while working and poor personal hygiene practices, and unsafe food and water consumption were associated with the risk of diarrhoeal episodes in adults. Improve personal hygiene practices and use of relevant treated wastewater and excreta as the public health measures to reduce these exposures will be most effective and are urgently warranted.